2016
DOI: 10.1063/1.4954222
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic high-field terahertz response of free-standing carbon nanotubes

Abstract: We demonstrate that unidirectionally aligned, free-standing multi-walled carbon nanotubes (CNTs) exhibit highly anisotropic linear and nonlinear terahertz (THz) responses. For the polarization parallel to the CNT axis, strong THz pulses induce nonlinear absorption in the quasi-one-dimensional conducting media, while no nonlinear effect is observed in the perpendicular polarization configuration. Time-resolved measurements of transmitted THz pulses and a theoretical analysis of the data reveal that intense THz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[220] the authors patterned periodic array of rectangular apertures on the CNT films with short aperture axis along CNTs www.advopticalmat.de orientation and observed an extraordinary transmission peaks in the THz spectra due to a coupling of the radiation polarized along the CNT alignment to the surface plasmon polaritons. Lee et al [227] studied free standing MW CNTs in high-field THz pulses and found an anisotropy both in linear and in nonlinear effects. Lee et al [227] studied free standing MW CNTs in high-field THz pulses and found an anisotropy both in linear and in nonlinear effects.…”
Section: Thz Response Of Carbon Nanotubesmentioning
confidence: 99%
“…[220] the authors patterned periodic array of rectangular apertures on the CNT films with short aperture axis along CNTs www.advopticalmat.de orientation and observed an extraordinary transmission peaks in the THz spectra due to a coupling of the radiation polarized along the CNT alignment to the surface plasmon polaritons. Lee et al [227] studied free standing MW CNTs in high-field THz pulses and found an anisotropy both in linear and in nonlinear effects. Lee et al [227] studied free standing MW CNTs in high-field THz pulses and found an anisotropy both in linear and in nonlinear effects.…”
Section: Thz Response Of Carbon Nanotubesmentioning
confidence: 99%
“…Recently, network films consisting of nanomaterials such as single-walled nanotubes (SWNTs), graphene, reduced graphene oxide, and silver nanowires (AgNWs) have emerged as a potential platform for optoelectronic devices 17 22 . Solution-based processes allow us to use relatively low-cost methods of spin-coating, roll-to-roll processing, and printing.…”
Section: Introductionmentioning
confidence: 99%
“…15 THz-TDS systems are powerful tools for material spectroscopy, layer inspection, and transmission imaging of packaged objects. 16 These capabilities of THz-TDS systems are utilized in authentication, [17][18][19] nondestructive inspection of composite materials, [20][21][22][23][24][25][26][27][28] threedimensional imaging, [29][30][31][32] metrology and quality control of industrial products, [33][34][35][36][37] detection of concealed weapons, [38][39][40][41][42][43][44][45] art investigations, 46,47 tomography, [48][49][50][51][52] biomedical diagnosis, [53][54][55][56] material characterization, [57][58][59][60][61][62] thickness measurement, …”
Section: Introductionmentioning
confidence: 99%